(untitled) (Heritage, 2021)
The subject of this work are the names of springs, streams and rivers which make up a tributary of the right basin of the Middle Ibar at the territory of the municipality Leposavić. The research covers hydronyms from Šaljska Bistrica all over to Bistrica which, in some way, represent a natural mark over which this municipality spreads around. The material is collected with the use of the field exploration and each of the hydronyms has an accent, so each is determined by a dialect. There have been three classifications according to the collected material. The first division, having in mind the shape of hydronyms, differentiates between those that are liquid and those that are still. The second one, called the structural, divides the hydronyms into single membered, two-membered and three-membered. A criterion of motivation for the third division divides hydronyms into those which are of physiogenic origin (natural names) and into those of anthropogenic origin (names created by men). Single membered hydronyms derived from nouns or derivation, most commonly by the suffixation.The greatest number of the two-membered hydronyms was created in the process of derivation with the adjectival suffix where the most productive suffix is that on -ski. Three-membered hydronyms have a well established structure: at the first place there is hydronymic appellation, at the second there is a preposition and at the third some of the appellations. Hydronyms with natural names imply the use of hydronymic and geographical appellations. Due to the origin of motivation, a group of hydronyms of anthroponimic origin differentiates much more than the others and even contains more subgroups. Diverse motivation when naming hydronyms is absent in all the groups while the most numbered hydronyms of toponymic origin have been created in the process of metonymy at the relation of place-name-hydronym